A World Apart: Global Inequality and its Consequences - Films Media Group (2007)
A growing number of environmentalists, ethicists, and economists believe that the needs of the "have-nots" will one day become too powerful to ignore. This program highlights that viewpoint, illustrating vast disparities between the living standards of developed and underdeveloped nations and questioning the wisdom of looking the other way. Deconstructing conventional economic notions of production and consumption, the film examines the role of Western corporations in environmental problems-such as deforestation, destructive mining, and land mine infestation in Africa, Asia, and South America. These problems are linked to global economic issues, such as lack of access to capital markets and dependence on foreign aid. (53 minutes).
fma39437
Mode of access: World Wide Web.
System requirements: Windows Media, etc.